2017
DOI: 10.1016/j.celrep.2017.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Adenomatous Polyposis Coli Defines Treg Differentiation and Anti-inflammatory Function through Microtubule-Mediated NFAT Localization

Abstract: Adenomatous polyposis coli (APC) is a polarity regulator and tumor suppressor associated with familial adenomatous polyposis and colorectal cancer development. Although extensively studied in epithelial transformation, the effect of APC on T lymphocyte activation remains poorly defined. We found that APC ensures T cell receptor-triggered activation through Nuclear Factor of Activated T cells (NFAT), since APC is necessary for NFAT's nuclear localization in a microtubule-dependent fashion and for NFAT-driven tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
63
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(74 citation statements)
references
References 65 publications
(90 reference statements)
5
63
3
Order By: Relevance
“…It increases the nuclear factor of activated T cells (NFAT) in a microtubule-dependent fashion. APC deficiency in mice reduced NFAT within the nucleus of intestinal regulatory T cells (Tregs), leaving a disturbed Treg differentiation together with anti-inflammatory cytokine, interleukin 10 (IL-10) [275]. APC migration in prostate cancer cells is induced by transforming growth factor beta 1 (TGF-b1) and regulated by Smad7 and p38 mitogen-activated protein kinase (p38 MAPK) [276].…”
Section: Chronic Inflammationmentioning
confidence: 99%
“…It increases the nuclear factor of activated T cells (NFAT) in a microtubule-dependent fashion. APC deficiency in mice reduced NFAT within the nucleus of intestinal regulatory T cells (Tregs), leaving a disturbed Treg differentiation together with anti-inflammatory cytokine, interleukin 10 (IL-10) [275]. APC migration in prostate cancer cells is induced by transforming growth factor beta 1 (TGF-b1) and regulated by Smad7 and p38 mitogen-activated protein kinase (p38 MAPK) [276].…”
Section: Chronic Inflammationmentioning
confidence: 99%
“…[53][54][55][56] Increased APC expression promotes differentiation of regulatory T cells and limits inflammatory responses. 57 Collectively, our findings suggest that biopsy specimens with MVI may be associated with a state of WNT pathway activation, whereas biopsy specimens with no major abnormalities may be associated with a state of WNT inhibition.…”
mentioning
confidence: 64%
“…In CD4 + T cells and endothelial cells, loss of DEPTOR leads to activation F I G U R E 5 Separate multivariate prognostic model for allograft failure. Increased APC expression promotes differentiation of regulatory T cells and limits inflammatory responses 57. The table lists the top 10 genes from the survival model ordered by decreasing magnitude of the strength of association (β-coefficient) between each gene and hazard for allograft failure.…”
mentioning
confidence: 99%
“…Recently, a novel role for APC mutated in reducing the action of the immune system has been suggested, preventing the control of intestinal inflammation. In particular, a deficiency in the APC protein reduces nuclear transcription factor NFAT, thereby preventing T-reg lymphocyte activation and then a failure in the control of local inflammation in the intestine [9]. Recent studies have shown that chronic inflammation and ROS production can activate the Wnt/β-catenin pathways, but the mechanisms involved remain unclear.…”
Section: Biomed Research Internationalmentioning
confidence: 99%
“…Altered microbiome composition is associated with signal activation involving mitochondria, or/and altered redox homeostasis, proinflammatory cytokines induction, and stimulation of the immune system [8]. It is well known that chronic inflammation and reactive oxygen species (ROS) production in the colon epithelium can impair the Wingless/ It (Wnt)/β-catenin [9] and/or base excision repair (BER) pathways [10,11], enhance a cascade of molecular reactions in cells, and alter the metabolic state of tissues and predispose to polyp development.…”
Section: Introductionmentioning
confidence: 99%